Macrocognition: From Theory to Toolbox - Klein, Gary; Wright, Corinne (Frontiers in Psychology, 2016)
We trace several trajectories—the evolution of field-based decision making models in the mid-1980s to the formation of the Naturalistic Decision Making movement in 1989, then the further broadening of NDM into Macrocognition in 2003, and finally the transition from macrocognitive models into a set of methods and tools to boost cognitive performance.